Professionals' perceptions on management practices supporting employee well-being in a diverse working community - Suoniemi, Anni (My University, 2024)
Over the past decade, employee well-being has gained higher focus in organizations. Professionals in knowledge-intensive work, are experiencing employee well-being challenges, such as stress and burnout, more than ever before. Organizations are now focusing more on employee well-being itself, rather than enhancing organizational performance through employee well-being initiatives. Meanwhile, organizations are struggling to retain and attract talent. Megatrends, such as globalization, demographical change, and technological advancements are also shaping work. Employees from diverse cultural, national, and educational backgrounds are being brought together. At the same time, workforce is aging, and organizations have employees from different generations working jointly. These changes place greater demands on managers, who must balance individual differences, while treating all employees equally, and managing conflicts that may arise from language barriers or differing interpretations. Considering all these factors, this thesis explores professionals’ perceptions on management practices that support employee well-being in a diverse working community. The literature review examines psychological well-being and work-related aspects to employee well-being to build comprehensive understanding of employee well-being. Literature review covers topics such as employee well-being management, employee-manager relationship, and transformational leadership to identify effective management practices for supporting employee well-being. The thesis also examines the idiosyncrasies of professional work and diversity in working community to unravel their impact on employee well-being. Professionals’ perceptions are at the core of this thesis. Literature review reveals that professionals’ perceptions are rarely studied in the field of business. This thesis uses qualitative research approach to shed light on new insights on professionals’ perceptions on employee well-being, professional work, and working in a diverse working community. Data is collected through interviewing professionals with diverse age-profiles, different genders, different numbers of experience in professional work, from different organizations and diverse working communities to gain as diverse representation of perceptions, as possible. A model for managers to support professionals’ employee well-being, developed by the author, is introduced in this thesis. The thesis offers both theoretical and practical implications for managers, academics, and psychologists. It suggests that management practices should aspire professionals to enjoy going to work, find their work meaningful and have a good work-life balance. This can be achieved by making work and working conditions supportive of employee well-being. Secondly, managers should commit to building and maintaining employee well-being, and finally, managers should get to know their employees on a personal level, to consider the needs of individuals. By examining professionals' perceptions on employee well-being, professional work, and diverse working community, the thesis expands understanding of these phenomena. These insights can be applied across various academic fields such as international business, management, and occupational healthcare.

Työhyvinvointi on noussut organisaatioissa entistä enemmän esille viimeisen vuosikymmenen aikana. Asiantuntijatyöntekijät, jotka tekevät tietointensiivistä työtä, kohtaavat työhyvinvoinnin haasteita, kuten stressiä ja loppuun palamista, enemmän kuin koskaan ennen. Organisaatiot keskittyvät nyt yksinomaan työhyvinvoinnin edistämiseen, sen sijaan että pääasiallisena tavoitteena olisi organisaation suorituskyvyn parantaminen työhyvinvoinnin kautta. Samaan aikaan organisaatioilla on haasteita pitää kiinni hyvistä työntekijöistä ja houkutella uusia osaajia. Myös megatrendit, kuten globalisaatio, väestörakenteen muutos ja teknologinen kehitys muokkaavat työtä. Monimuotoiset ja monikansalliset työntekijät erilaisista kulttuuri- ja koulutustaustoista työskentelevät yhdessä. Samaan aikaan työvoima ikääntyy ja organisaatioissa työskentelee yhdessä eri sukupolvien edustajia. Nämä muutokset luovat esihenkilöille entistä suurempia vaatimuksia. Esihenkilöiden tulee löytää tasapaino siinä, miten he huomioivat työntekijät yksilöllisesti, samalla kuitenkin kohdellen heitä tasa-arvoisesti. Esihenkilöiden on myös hallittava ja johdettava kielimuureista ja erilaisista tulkinnoista syntyviä konflikteja. Huomioiden edellä mainitut tekijät, tässä pro gradu-tutkielmassa tutkitaan asiantuntijatyöntekijöiden käsityksiä työhyvinvointia tukevista johtamiskäytänteistä monimuotoisessa työyhteisössä. Kirjallisuuskatsauksessa tarkastellaan psyykkisen hyvinvoinnin ja työhön liittyvien tekijöiden vaikutusta työhyvinvointiin. Kirjallisuuskatsauksessa käsitellään myös työhyvinvoinnin johtamista, työntekijä-esihenkilösuhdetta sekä transformatiivista johtamista, joiden avulla tunnistetaan työhyvinvointia tukevia johtamiskäytänteitä. Lisäksi tutkimuksessa tarkastellaan asiantuntijatyötä ja työyhteisön monimuotoisuutta, jotta ymmärretään niiden vaikutukset työhyvinvointiin. Asiantuntijatyöntekijöiden näkemykset ovat tämän tutkimuksen keskiössä. Kirjallisuuskatsauksen myötä selviää, ettei asiantuntijatyöntekijöiden näkemyksiä ole juurikaan tutkittu kirjallisuudessa. Tässä tutkimuksessa laadullista tutkimusmenetelmää hyödyntäen valotetaan asiantuntijoiden näkemyksiä työhyvinvointiin, asiantuntijatyöhön ja työskentelyyn monimuotoisessa työyhteisössä. Aineisto kerätään haastattelemalla erilaisia asiantuntijatyöntekijöitä, jotta erilaiset näkemykset tulevat mahdollisimman monipuolisesti esille. Haastateltavat edustavat eri ikäprofiileja ja sukupuolia. Lisäksi he työskentelevät eri toimialoilla, organisaatioissa ja työyhteisöissä. Tutkimuksessa esitellään myös kirjoittajan esihenkilöille luoma malli, jonka avulla voidaan tukea työhyvinvointia. Tutkimus tarjoaa sekä teoreettista että käytännöllistä kontribuutiota esihenkilöille, johtajille, tutkijoille ja psykologeille. Johtamiskäytänteillä tulisi pyrkiä siihen, että asiantuntijatyöntekijät menevät mielellään töihin, kokevat työnsä mielekkääksi sekä saavuttavat työn ja vapaa-ajan tasapainon. Pyrkimykseen voidaan päästä tekemällä työstä ja työoloista työhyvinvointia tukevia. Lisäksi esihenkilöiden tulee sitoutua työhyvinvoinnin rakentamiseen ja ylläpitoon, sekä tutustua työntekijöihin henkilökohtaisesti, jotta yksilölliset tarpeet saadaan huomioitua työssä. Tutkimus asiantuntijatyöntekijöiden näkemyksistä työhyvinvointiin, asiantuntijatyöhön ja työyhteisön monimuotoisuuteen laajentaa yleistä ymmärrystä näistä aiheista. Oivalluksia voidaan soveltaa useilla akateemisilla aloilla, kuten kansainvälisessä liiketoiminnassa, johtamisessa ja työterveyden alalla.
Keywords: employee well-being, meaningful work, work-life balance, employee-manager relationship, transformational leadership, management practices, professional work, flexible work, diverse working community